Kinematika in dinamika: učbenik - Vesenjak, Matej; Kegl, Marko (2017)
Kinematics and Dynamics. učbenik. The textbook was introduced as didactic support for the subject Kinematics and dynamics at the Faculty of Mechanical Engineering, University of Maribor. A basic level of knowledge in the field of statics and mathematics is expected to comprehend the book of solved problems and exercises.
Keywords: mechanics; kinematics; relative motion; dynamics; vibrations